43 Enhanced Collagen Type I Synthesis of Tenocytes by Periodic in vitro Mechanical Stimulation. (5th September 2014) - Huisman, Elise; Lu, Alex; McCormack, Robert; Scott, Alex
Abstract : Introduction: Mechanical stimulation (e.g. slow heavy loading) has proven beneficial in the rehabilitation of chronic tendinopathy, however the optimal parameters of stimulation have not been experimentally determined. Desensitisation to continuous load cycles is a phenomenon that occurs in bone cells. More importantly, introducing rest insertion periods during mechanical stimulation restored the mechanosensitivity in bone cells (Robling, 2001). In this study of mechanically stimulated human tenocytes, the influence of rest insertion and cycle number on 1 the protein and mRNA levels of type I and III collagen; 2 the mRNA levels of transforming growth factor beta ( TGFB1 ) and scleraxis ( SCXA ); and 3 tenocyte morphology, were assessed. Methods: Human hamstring tenocytes were mechanically stimulated using a Flexcell system. The stimulation regimens were 1) continuous and 2) rest-inserted cyclic equiaxial strain at a frequency of 0.1Hz for 100 or 1000 cycles. qPCR was performed to determine relative mRNA levels and automated quantitative immunocytochemistry image analysis was used to assess protein levels and cell morphology. Results: Collagen type I mRNA level and pro-collagen protein levels were higher in tenocytes that were subjected to rest-inserted mechanical stimulation, compared to continuous loading (p < 0.05). Rest insertion and cycle number also had significant positive effects on the levels of mRNA for TGFB1 and SCXA (p < 0.05). Cells undergoing mechanical stretching had a lower major/minor axis (more rounded, p < 0.05), and a higher solidity (more branched, p < 0.01) compared to unstimulated controls. Discussion: The incorporation of rest periods in a mechanical loading regimen results in greater collagen type I synthesis, which is in line with Robling et al. (Robling, 2001). Mechanical stresses applied to the cells lead to altered forces within the cell which play important roles in the control of cell shape and function (Chicurel, 1998; Maniotis, 1997). In this study there was no direct relation between cell morphology and gene expression, however mechanical stimulation, overall, induced a metabolically active tenocyte phenotype as evidenced by cells that were more rounded, were more branched and with higher expression levels of SCXA (p < 0.05). An implication of these findings may be that rest periods incorporated in stretch cycles in a chronic tendinopathy rehabilitation program may induce a substantial adaptive response. References: Chicurel, et al . Curr Opin Cell Biol. 1998;10:232–239 Maniotis, et al . Proc Natl Acad Sci USA. 1997;94:0849–854 Robling et al . J Exp Biol. 2001;204:3389–3399